1960
DOI: 10.1161/01.cir.22.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Enlargement in Chronic Severe Anemia

Abstract: One hundred and fifty patients with chronic severe anemia were studied to determine the nature of cardiac enlargement and its relation to various factors. Enlargement was present in 120 patients. It showed no consistent relation to the hemoglobin level on admission. A significant increase in the cardiac size and incidence of failure was observed with increased severity of anemia, and in female as compared to male patients. The incidence of enlargement showed no relation to the age and sex of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, other symptoms and signs resulting from hypoxic functioning occurred after physical activity, such as fatigue, exertional dyspnoea progressing to breathlessness at rest, and vertigo. In previously published studies ( 18 , 19 ), cardiac functional damage was determined by X-ray and conventional echocardiography in patients with anemia; it was found that cardiac enlargement, LV hypertrophy, and heart dysfunction are common in patients with chronic severe anemia. It is difficult to diagnose cardiac damage at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, other symptoms and signs resulting from hypoxic functioning occurred after physical activity, such as fatigue, exertional dyspnoea progressing to breathlessness at rest, and vertigo. In previously published studies ( 18 , 19 ), cardiac functional damage was determined by X-ray and conventional echocardiography in patients with anemia; it was found that cardiac enlargement, LV hypertrophy, and heart dysfunction are common in patients with chronic severe anemia. It is difficult to diagnose cardiac damage at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Sanghvi et al reported that 120 of 155 patients reported cardiac enlargement by chest X-ray, and enlargement disappeared rapidly in 92 patients with correction of the anemia in 1960 [9]. More recently than previous study, Naito et al showed that chronic iron-deficiency anemia leads to LV hypertrophy and HF in molecular level among animals [10].…”
Section: Discussionmentioning
confidence: 97%
“…Among them, chronic anemia is a major cause of high cardiac output state which we easily encounter in daily practice [8]. However, there are only few studies exist which evaluating cardiac enlargement [9] or clinical implications [10,11] in patients with chronic anemia. Most recently, Hammoudi et al reported that LA volume is not an index of LV diastolic dysfunction in patients with sickle cell anemia [12], however, sickle cell anemia is very rare in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…2 Severe anemia is associated with a high incidence of cardiac enlargement and may result in congestive heart failure. 3,4 Chronic severe anemia is known to increase cardiac output when hemoglobin levels drop to < 7 g/dL for three months or more duration. 5 Cardiac enlargement in patients with chronic severe anemia has been reported in necropsy studies.…”
mentioning
confidence: 99%
“…In addition, cardiac enlargement has been attributed to dilatation or hypertrophy. 3 Chest roentgenogram is routinely used to assess the presence cardiac enlargement. The aim of our study was to determine the relationship between hemoglobin level and cardiothoracic ratio in children with chronic severe anemia.…”
mentioning
confidence: 99%